IDENTIFICATION AND DISTRIBUTION OF FISH FAUNA IN SHAFARUD RIVER, GUILAN PROVINCE - K. Abbasi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2007)
Shafarud river is lied in south-west Caspian Sea and it is important for spawning of anadromous fishes, feeding and spawning of estuary fishes and special fish population. Studied fishes have been sampled in 7 stations from river mouth to upstream from Fall 2001 until summer 2002 and electroschoker, cast net and beach seine were used to catch them and main purposes of this study were: determining fish diversity, abundance and their spatial and temporal distribution and present role of the river in restocking migratory and estuary fish species. The study on 1912 specimens showed 21 species and subspecies fish belong to 8 families. Cyprinidae family with 10 species and abundance 62.87 % of total populations was dominant in all stations and seasons. Among the identified species, Neogobius kessleri, Capoeta capoeta gracilis, Albumoides bipunctatus and Barbus lacerta cyri that are native and river resident had the most dispersion and the fish with 25/58 , 20/61 , 19/87 and 8/37 percent of total sampeled fish, had respectively the most abundance in the river. There were 11 species of freshwater resident species, 6 species of marine or estuary fishes and 4 species of migratory or anadromous fishes in Shafarud River and in the river were identified 5 species of alein fishes, too. In general, the study showed the river have good potential in restocking of migratory fishes and its stuary is suitable for feed and growth of marine species fingerling.